2002
DOI: 10.1046/j.1464-5491.2002.00711.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis following first acute myocardial infarction in Type 2 diabetes: a comparative population study

Abstract: Among hospitalized patients with first acute myocardial infarction, Type 2 diabetes mellitus is consistently associated with increased mortality and increased hospital admission for heart failure. The estimated 4-year survival rate is only 50%. Our results indicate that younger subjects with Type 2 diabetes and acute myocardial infarction are a high-risk group deserving of special study, and support the argument for aggressive targeting of coronary risk factors among patients with Type 2 diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
0
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 25 publications
1
49
0
2
Order By: Relevance
“…4,5 Patients with type 2 diabetes not only have more extensive cardiovascular disease (CVD), but they also have a higher prevalence of hypertension, heart failure, peripheral vascular disease, and neuropathy. 6 Type 2 diabetes is an independent risk factor for all types of CVDs, as well as long-term mortality and need for revascularization.…”
mentioning
confidence: 99%
“…4,5 Patients with type 2 diabetes not only have more extensive cardiovascular disease (CVD), but they also have a higher prevalence of hypertension, heart failure, peripheral vascular disease, and neuropathy. 6 Type 2 diabetes is an independent risk factor for all types of CVDs, as well as long-term mortality and need for revascularization.…”
mentioning
confidence: 99%
“…A number of studies have found relationships between the macrovascular (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30) and microvascular complications of diabetes and mortality. However, many of these studies assessed complications individually, failing to consider other putative risk factors and complications.…”
mentioning
confidence: 99%
“…Third, our study population was derived from 6 hospitals diverse in payer status, age, race/ethnicity, and socioeconomic status, increasing the potential generalizability of our findings. Fourth, our models are less likely to be overfit to the idiosyncrasies of our data given that the predictors in our final AMI‐specific models have good clinical face validity, and have been associated with adverse outcomes, particularly mortality, in prior studies of this population 28, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39…”
Section: Discussionmentioning
confidence: 99%